Rivaroxaban versus low molecular weight heparin for managing lower extremity deep vein thrombosis following thoracoscopic lung cancer surgery: a randomized controlled trial - Lidan Zhang; Di Wu; Liang Li; Qin Zhao; Hailing Yang; Xiaoyong Han; Liang Liu; Lu Gao (Journal of Cardiothoracic Surgery)
Abstract Objective To assess the effectiveness and safety profiles of rivaroxaban compared to low molecular weight heparin (LMWH) in managing lower extremity deep vein thrombosis (DVT) subsequent to thoracoscopic lung cancer surgery. Methods Sixty patients diagnosed with lower extremity deep vein thrombosis (DVT) following thoracoscopic lung cancer surgery were randomly assigned to two groups: the experimental group comprising 30 patients treated with rivaroxaban, and the control group consisting of 30 patients treated with low molecular weight heparin (LMWH). The fundamental clinical characteristics of patients in both groups were documented, encompassing parameters, along with pre- and post-surgical lower limb vascular ultrasound findings. Additionally, variations in drainage volume over the initial three days following the procedure were also noted. Patients were subjected to a three-month follow-up period, during which data from one-month and three-month postoperative examinations were collected. Results Patients from both groups exhibited satisfactory wound healing postoperatively. D-dimer levels remained stable, and lower extremity vascular ultrasound evaluations showed no signs of additional thrombus formation. Moreover, there were no reported cases of distant postoperative complications such as pleural effusion, gingival bleeding, or gastrointestinal bleeding. Nonetheless, subcutaneous bruising was observed in six patients from the control group, all localized at the sites of LMWH injections. Conclusion Rivaroxaban demonstrates efficacy comparable to LMWH in patients with lower extremity deep vein thrombosis following thoracoscopic lung cancer surgery, while exhibiting a superior safety profile compared to LMWH.